2005
DOI: 10.1021/ja0550475
|View full text |Cite
|
Sign up to set email alerts
|

An NMR Determination of CO Diffusion on Platinum Electrocatalysts

Abstract: Study of the diffusion of small molecules on catalyst surfaces is of broad general interest, and there have been numerous investigations of surface CO diffusion on Pt under ultrahigh vacuum (UHV) or gas phase conditions. 1-7 Both diffusion coefficients (D CO ) as well as activation energies (E d ) for diffusion have been measured and are of importance in the context of, among other topics, CO hydrogenation in fuel synthesis 8 and CO oxidation in heterogeneous catalysis. 9 The latter topic is also of interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 20 publications
(62 reference statements)
5
76
1
Order By: Relevance
“…recombination step. For the intermediate particles (3.3 nm), the overall activity is limited by on-site kinetics at small E and by diffusion at large E; the transition occurs at E % 0:8 V. These findings for the particle size effect on CO ad mobility are in line with NMR experiments [97,98].…”
Section: Modeling Of Particle Size Effects In Co Ad Electrooxidationsupporting
confidence: 80%
See 1 more Smart Citation
“…recombination step. For the intermediate particles (3.3 nm), the overall activity is limited by on-site kinetics at small E and by diffusion at large E; the transition occurs at E % 0:8 V. These findings for the particle size effect on CO ad mobility are in line with NMR experiments [97,98].…”
Section: Modeling Of Particle Size Effects In Co Ad Electrooxidationsupporting
confidence: 80%
“…This corresponds to a lowering of the surface mobility on the small particles by a factor $10 3 . Using NMR spectroscopy, Kobayashi et al found that the tracer diffusion coefficient of adsorbed CO ad at electrolyte-immersed Pt black particles (5.5 nm), D CO ¼ 3:6 Á 10 À13 cm 2 =s 1 , is considerably lower than the value for single crystalline surfaces [98]. The theoretical model presented in References 26 and 99 employed the active-site concept to investigate reaction rate distributions on heterogeneous surfaces of Pt nanoparticles.…”
Section: Modeling Of Particle Size Effects In Co Ad Electrooxidationmentioning
confidence: 99%
“…Upon decreasing the particle size from above 5 nm to 1.8 nm, CO ads electrooxidation kinetics slows down, as manifested by the increase in the time of the current maxima and the decrease in their amplitude, concomitant with a pronounced current tailing on the descending slope of the transient, strongly deviating from the transients reported for extended surfaces [Andreaus et al, 2006;Arenz et al, 2005;Kobayashi et al, 2005;Maillard et al, 2004aMaillard et al, , 2007b. Most remarkable are the size-dependent changes in the shape of the transient (Fig.…”
Section: Influence Of Particle Size On Electrocatalytic Activities: Cmentioning
confidence: 76%
“…As CO and OH are required to be at adjacent sites to react, its efficiency depends on the surface diffusion of species. This has been shown to be a fast process for CO on Pt [46,47]. Many metals have been used to form bimetallic catalysts with Pt and enhance its catalytic properties for methanol electro-oxidation, like W, Sn and Mo [48];…”
Section: Pt-based Catalysismentioning
confidence: 99%